2019
DOI: 10.4012/dmj.2017-438
|View full text |Cite
|
Sign up to set email alerts
|

Early bond strengths of 4-META/MMA-TBB resin cements to CAD/CAM resin composite

Abstract: The purpose of this study was to evaluate the early tensile bond strengths of three different resin cements; Super Bond C&B (conventional and quick type) and ResiCem to a CAD/CAM composite block. A CAD/CAM composite block (Shofu Block HC) was ground and silanized according to the manufacturers' instructions before cementation. A conventional tensile bond strength test (Ø: 4 mm) was performed 10 min, 1 h and 24 h after bonding. Super Bond C&B (quick type) showed the highest bond strength at 24 h. However, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…No previous studies have examined the effect of different types of restoration (i.e., inlay, onlay, and crown) on the µ-TBS, especially the µ-TBS obtained from the intra-cavity wall after a dynamic load. Evaluations of the bond strength mainly focused on the mean value of the µ-TBS [4][5][6]9,10,16,17) . This is a quantitative evaluation that is easy to understand, because the magnitude of the obtained data can be simply related to the bond strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No previous studies have examined the effect of different types of restoration (i.e., inlay, onlay, and crown) on the µ-TBS, especially the µ-TBS obtained from the intra-cavity wall after a dynamic load. Evaluations of the bond strength mainly focused on the mean value of the µ-TBS [4][5][6]9,10,16,17) . This is a quantitative evaluation that is easy to understand, because the magnitude of the obtained data can be simply related to the bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Both are useful as luting materials for not only metal-free but also metal restoratives. Previous studies focused on the tensile bond strength have reported that both cement systems demonstrate different bonding behaviors to human dentin 4) and CAD/ CAM composite blocks 5) . The microtensile bond strength (µ-TBS) test developed by Sano et al 6) is an effective means of investigating the internal bond strength that is influenced by various intraoral stresses, such as thermal and cyclic load stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation is that the luting procedure, using adhesive luting agents, is technically demanding and could affect bonding performance. In addition, the resin-based CAD/CAM materials are pre-fabricated and completely polymerized by the manufacturer, which means a poor oxygen-inhibited layer is present on the surface of the materials [14]. Moreover, several studies indicated that the hoop stress that originated at the circumference of the restorations with occlusal forces led to the loosening of the restorations [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…This debonding failure is attributed to poor adhesion of the CAD/CAM composites or incompatible preparation of the crown material and abutment tooth 10,11,15) . To overcome this issue, many fundamental studies have been conducted to elucidate the adhesive properties of the CAD/CAM composites [16][17][18] . For the bonding protocol of the CAD/CAM composites, several studies and manufacturers' instructions suggested that composite crowns should be subjected to alumina airborne-particle abrasion followed by application of a primer containing a silane-coupling agent (hereafter silane primer) [18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%